2018
DOI: 10.1063/1.5010184
|View full text |Cite
|
Sign up to set email alerts
|

Review and perspective: Sapphire optical fiber cladding development for harsh environment sensing

Abstract: The potential to use single-crystal sapphire optical fiber as an alternative to silica optical fibers for sensing in high-temperature, high-pressure, and chemically aggressive harsh environments has been recognized for several decades. A key technological barrier to the widespread deployment of harsh environment sensors constructed with sapphire optical fibers has been the lack of an optical cladding that is durable under these conditions. However, researchers have not yet succeeded in incorporating a high-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(52 citation statements)
references
References 80 publications
0
52
0
Order By: Relevance
“…We can achieve total reflection by adjusting the refractive index of the claddings so as to reduce the propagation loss caused by particulates and contaminants from the surrounding media [40]. Excellent cladding materials must possess a refractive index lower than the core and a thermal expansion coefficient close to that of core materials, while simultaneously exhibit thermo-chemical and mechanical stability [41]. The best approaches thus far are summarized below.…”
Section: Single Crystal Fiber Cladding Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…We can achieve total reflection by adjusting the refractive index of the claddings so as to reduce the propagation loss caused by particulates and contaminants from the surrounding media [40]. Excellent cladding materials must possess a refractive index lower than the core and a thermal expansion coefficient close to that of core materials, while simultaneously exhibit thermo-chemical and mechanical stability [41]. The best approaches thus far are summarized below.…”
Section: Single Crystal Fiber Cladding Approachesmentioning
confidence: 99%
“…The researchers also calculated through numerical simulations the optimal size of the voids needed to improve light propagation. The ion implantation cladding method changes the refractive index of the surface of the crystal fiber and avoids the delamination of claddings, which is beneficial for applications in harsh environments [41].…”
Section: Ion Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous fiber cladding, especially with axially aligned pore channels such as in microstructured optical fiber (also termed photonic crystal fiber [PCF]), affords endless degrees of freedom in structural and hence fiber optic property manipulation . This breakthrough development has led to the advent and continued expansion of new classes of special optical fiber with novel functionalities for applications not possible with conventional optical fiber . We have recently reported that anodic aluminum oxide (AAO) cladding with radially aligned nanoscopic pore channels can be produced on silica and sapphire optical fiber by anodization of aluminum deposited on the fiber surface .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This breakthrough development has led to the advent and continued expansion of new classes of special optical fiber with novel functionalities for applications not possible with conventional optical fiber. [6][7][8][9] We have recently reported that anodic aluminum oxide (AAO) cladding with radially aligned nanoscopic pore channels can be produced on silica and sapphire optical fiber by anodization of aluminum deposited on the fiber surface. [10][11][12] Compared with conventional optical fiber and PCF, AAO-clad fiber, given the unique cladding structure and tunable index of refraction, has the following distinct advantages.…”
Section: Introductionmentioning
confidence: 99%